Attitude towards the patient with a nasopharyngeal mass - differences in the ENT doctor’s approach in Portugal - Correia de Oliveira, Mafalda (2022)
Aim: The nasopharynx is an anatomical region where diverse tumors arise. They are mostly benign, with the most common malignant one being carcinoma, followed by lymphoma. Nasal endoscopy with biopsy is the gold-standard in the diagnosis of these lesions. The aim of this study was to evaluate the differences in each ENT doctor’s approach in two different clinical cases of patients with a nasopharyngeal mass. Material and Methods: Release of an online questionnaire with two different cases of patients with a nasopharyngeal mass and their respective endoscopy, comprising 3 questions for each case about each individual doctor’s approach to the patient. Results and Conclusion: Despite knowing that all suspicious lesions should be biopsied, there was no consensus in the participants of this study on the approach to these patients, neither as to what for them defines a mass as suspicious nor the timing at which they would request imaging complementary studies.